Drying kinetics of frozen oyster mushrooms (Pleurotus ostreatus) - Ohaco Dominguez, Elizabeth Haydee (2016)
The kinetics of drying of frozen oyster mushrooms (Pleurotus ostreatus) was evaluated. Air temperatures of 50 C, 60 C and 70 C, at 2 m/s and 5% relative humidity, were used for drying experiments. In this work, we studied different mathematical models representing mushroom drying kinetics in order to select the best model for drying curves. Statistics used for comparison and selection of models were based on residual standard error and Akaike’s information criterion. From all models evaluated, Page was selected as the best model on the basis of its simplicity and good fit of experimental data. The effective diffusivity coefficient (Deff) and the activation energy (Ea) were calculated for working conditions. The Deff ranged from 6.64 x 10-10 to 1.024 x 10-8 m2 /s for the temperature range studied. The Ea for the diffusion water was 23.02 kJ/mol.